Políticas públicas de salud sexual y reproductiva en el Perú: el ingreso de la reglamentación del aborto terapéutico en la agenda política gubernamental - Leiva Rioja, Zoila (2016)
The objective of the present article is to analyze the process of introducing the regulation of therapeutic abortion into the peruvian governmental agenda, identifying the factors that came together to generate such event, the period of study being between the years 2005 to 2014. The investigation corroborates that said event was possible due to the confluence of certain political and institutional factors on the national stages, the strategy of groups in favor (pro-choice) and against (pro-life) the regulation, and international influence.